Propionic acid : method of production, current state and perspectives - Ranaei, Vahid (Array, 2020)
During the past years, there has been a growing interest in the bioproduction of propionic acid by Propionibacterium. One of the major limitations of the existing models lies in their low productivity yield. Hence, many strategies have been proposed in order to circumvent this obstacle. This article provides a comprehensive synthesis and review of important biotechnological aspects of propionic acid production as a common ingredient in food and biotechnology industries. We first discuss some of the most important production processes, mainly focusing on biological production. Then, we provide a summary of important propionic acid producers, including Propionibacterium freudenreichii and Propionibacterium acidipropionici, as well as a wide range of reported growth/production media. Furthermore, we describe bioprocess variables that can have impact on the production yield. Finally, we propose methods for the extraction and analysis of propionic acid and put forward strategies for overcoming the limitations of competitive microbial production from the economical point of view. Several factors influence the propionic acid concentration and productivity such as culture conditions, type and bioreactor scale; however, the pH value and temperature are the most important ones. Given that there are many reports about propionic acid production from glucose, whey permeate, glycerol, lactic acid, hemicelluloses, hydrolyzed corn meal, lactose, sugarcane molasses and enzymatically hydrolyzed whole wheat flour, only few review articles evaluate biotechnological aspects, i.e. bioprocess variables.